Taxonomy of human-system interaction challenges for metaverse integration in industrial maintenance - Khanna, Parul; Karim, Ramin; Tretten, Phillip (Frontiers in Virtual Reality, 2026)
The metaverse is an emerging technological shift that enhances collaboration, telepresence, and decision-making, and can revolutionise industrial maintenance practices. While immersive technologies, such as Extended Reality (XR) encompassing Virtual Reality (VR), Augmented Reality (AR), and Mixed Reality (MR), are widely applied in domains like gaming, healthcare, and education, their adoption in industrial workflows remains limited. Its development and implementation carry challenges, especially from a Human-System Interaction (HSI) perspective. The purpose of this research is to understand the key technological issues and challenges associated with the implementation and use of the metaverse in industrial maintenance from an HSI perspective. This study employs a structured, systematic literature review focusing on the metaverse, as enabled by immersive technologies, in the context of industrial maintenance. The reviewed literature was analysed using thematic qualitative analysis to identify recurring HSI-related challenges and to develop a taxonomy categorising these challenges. The analysis resulted in a taxonomy comprising seven key challenge categories: usability, data management, accessibility, user experience (UX), technological performance, environmental and contextual awareness, and trust and transparency. The findings highlight UX as the core factor influencing adoption, as most challenges directly or indirectly impact user experience. The findings indicate that addressing these challenges can enable intuitive, transparent, and reliable metaverse systems tailored to industrial needs. However, advancing the industrial metaverse will require an interdisciplinary approach that combines engineering, human factors, data science, and design to deliver systems that are both technologically advanced and human-centred.